2018
DOI: 10.4187/respcare.06034
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Clinical Factors and Exclusion Criteria on Mortality in ARDS Observational Studies and Randomized Controlled Trials

Abstract: ARDS has a high mortality in the acute setting, with long-term disability among disease survivors. In 1967, David Ashbaugh and colleagues first described the clinical features of ARDS, which were notably similar to the infantile respiratory distress syndrome. Half a century later, ARDS remains underrecognized and is associated with high mortality rates. Valuable insights from observational studies fail to demonstrate a mortality benefit in randomized controlled trials (RCTs). In the absence of a pharmacologic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 56 publications
2
31
1
Order By: Relevance
“…The use of an ARDS-associated mechanical ventilator is a key treatment of patients with ARDS; however, it may cause ARDS-associated ventilator-induced lung injury and pulmonary fibrosis. A previous study indicated that have indicated that pulmonary fibrosis is closely related to mortality, prognosis and quality of life in patients with ARDS (12). However, to date, the cellular mechanisms of pulmonary fibrosis in patients with ARDS have remained to be clarified and the clinical prevention and treatment effects are not satisfactory.…”
Section: Discussionmentioning
confidence: 99%
“…The use of an ARDS-associated mechanical ventilator is a key treatment of patients with ARDS; however, it may cause ARDS-associated ventilator-induced lung injury and pulmonary fibrosis. A previous study indicated that have indicated that pulmonary fibrosis is closely related to mortality, prognosis and quality of life in patients with ARDS (12). However, to date, the cellular mechanisms of pulmonary fibrosis in patients with ARDS have remained to be clarified and the clinical prevention and treatment effects are not satisfactory.…”
Section: Discussionmentioning
confidence: 99%
“…The acute respiratory distress syndrome (ARDS) is a complex and deadly disease characterized by inflammation and lung permeability leading to alveolar edema, hypoxemia, and organ failure [1, 2]. ARDS occurs in up to 10% of patients admitted to an intensive care unit with mortality rates ranging from 35 to 46% [3, 4]. To date, there are no approved pharmacological treatments for this syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…The first and most common method was to consider EOL decisions as non-inclusion criteria (99% of the 61 articles); however, this method of data management leads to questions regarding how representative the selected population is since not including approximately half of the patients dying in ICUs in some pathologies could potentially diminish the relevance of the results [7]. The second point is that not including patients affected by EOL decisions does not avoid the potential need for EOL decisions during the study or follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the decision to withhold or withdraw treatment and other EOL decisions may greatly influence the immediate mortality rate and, therefore, could potentially modify the results of ICU studies, especially randomized controlled trials (RCTs), by over- or under-estimating mortality depending on how EOL decisions are considered in the study and/or in the analysis [7,8]. To the best of our knowledge, there is a lack of methodological guidance on how to correctly describe and manage data affected by EOL decisions.…”
Section: Introductionmentioning
confidence: 99%